Conclusion to carceral communities: struggle and carnival in Latin America’s carceral worlds - Antillano, Andrés (Carceral communities in Latin America, 2021)
This is an overarching reading of the diverse contributions to this volume. Departing from Mikhail Bajtin’s discussion of carnival, we reject the “pornographic” images (Bourgois) about Latin American prisons, to then offer an understanding based on existing tensions, struggles, and historical legacies. These works show the reconfiguration of the carceral worlds in the last few decades: new institutional arrangements between state actors; disputes over the political use of the prison; inmate-driven transformations in the internal order; redefinitions of the “inside/outside” relationships. Changes can be understood as a result of the processes of “reconfinement” and extension of imprisonment in recent decades; but also, as an effect of changes in the internal regime and, above all, in the configuration of the subaltern classes. From a distance, mutations are consequences of Neoliberal policies in the region, the War on Drugs, and more widely, the legacy of colonial and postcolonial relations.